METODE MUHAMMAD NASHIRUDDIN AL-ALBANI DALAM MENDAIFKAN HADIS: TELAAH KITAB DAIF SUNAN ABU DAUD - Aufi Izzadine; Nur Kholis bin Kurdian; Muhammad Haikal Ali Basyarahil (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2023)
Sunan Abu Dawud is one of the six main hadith books in the Sunni hadith tradition. This book was compiled by Imam Abu Dawud Sulaiman bin al-Ash'ath al-Sijistani in the 3rd century Hijriyah. This book contains hadiths related to Islamic law, arranged based on fiqh chapters. On the other hand, Sheikh Muhammad Nasiruddin al-Albani was a hadith scholar in the 20th century who was famous for his dedication to studying and assessing the authenticity of hadiths contained in classical hadith books, in addition to sahihain. In the context of Daif Sunan Abu Dawud, al-Albani filtered the hadiths contained in the book of Sunan Abu Dawud, separating the hadiths that were considered weak from those that were authentic or hasan. The hadiths that were considered authentic or hasan were then collected by him in a separate book called